Women's experiences of transfer from primary maternity unit to tertiary hospital in New Zealand: part of the prospective cohort Evaluating Maternity Units study. Issue 1 (December 2015) - Grigg, Celia; Tracy, Sally; Schmied, Virginia; Monk, Amy; Tracy, Mark
Abstract Background There is worldwide debate regarding the appropriateness and safety of different birthplaces for well women. The Evaluating Maternity Units (EMU) study's primary objective was to compare clinical outcomes for well women intending to give birth in either a tertiary level maternity hospital or a freestanding primary level maternity unit. Little is known about how women experience having to change their birthplace plans during the antenatal period or before admission to a primary unit, or transfer following admission. This paper describes and explores women's experience of these changes-a secondary aim of the EMU study. Methods This paper utilised the six week postpartum survey data, from the 174 women from the primary unit cohort affected by birthplace plan change or transfer (response rate 73 %). Data were analysed using descriptive statistics and thematic analysis. The study was undertaken in Christchurch, New Zealand, which has an obstetric-led tertiary maternity hospital and four freestanding midwife-led primary maternity units (2010–2012). The 702 study participants were well, pregnant women booked to give birth in one of these facilities, all of whom received continuity of midwifery care, regardless of their intended or actual birthplace. Results Of the women who had to change their planned place of birth or transfer the greatest proportion of women rated themselves on a Likert scale as unbothered by the move (38.6 %); 8.8 % were 'very unhappy' and 7.6 % 'very happy' (quantitative analysis). Four themes were identified, using thematic analysis, from the open ended survey responses of those who experienced transfer: 'not to plan', control, communication and 'my midwife'. An interplay between the themes created a cumulatively positive or negative effect on their experience. Women's experience of transfer in labour was generally positive, and none expressed stress or trauma with transfer. Conclusions The women knew of the potential for change or transfer, although it was not wanted or planned. When they maintained a sense control, experienced effective communication with caregivers, and support and information from their midwife, the transfer did not appear to be experienced negatively. The model of continuity of midwifery care in New Zealand appeared to mitigate the negative aspects of women's experience of transfer and facilitate positive birth experiences.